2005
DOI: 10.1149/1.1825292
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Direct CVD Oxides to Thermal Oxide Wafer Bonding in Silicon Layer Transfer

Abstract: The bonding strength of low-pressure chemical vapor deposition and plasma-enhanced chemical vapor deposition ͑PECVD͒ oxides to thermal oxide is studied. Prior to bonding, all CVD oxide wafers are subjected to careful surface preparation including densification, chemical-mechanical polishing, activation, and post-bond annealing to ensure high-quality bonding. All wafers show surface roughness and wafer bow suitable for bonding after the surface preparations. It is found that bonding strength increases upon anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Low temperature PECVD oxide layers offer a solution to this problem. Studies have confirmed that with proper layer preparation PECVD oxide bonding can be achieved (6,7).…”
Section: Introductionmentioning
confidence: 84%
“…Low temperature PECVD oxide layers offer a solution to this problem. Studies have confirmed that with proper layer preparation PECVD oxide bonding can be achieved (6,7).…”
Section: Introductionmentioning
confidence: 84%
“…Extremely low surface roughness is essential for high quality bonding due to higher contact area between the pairing wafers. 3,17 Oxygen (O 2 ) plasma activation is widely used in wafer bonding for bond strength enhancement at low temperature. 18 In order to determine if O 2 plasma activation can enhance the Ge-Ge bond strength, the Ge/Si wafers were split into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…An oxide-to-oxide bond is utilized to fuse the two wafers together. 6 The bond process begins by cleaning the wafer pairs and then exposing them to an oxygen plasma. The wafers are then brought into forced contact and annealed to strengthen the bond.…”
Section: Methodsmentioning
confidence: 99%